Effects of Intraperitoneal Zoledronic Acid Administration on Cerebral Vasospasm Following Experimental Subarachnoid Hemorrhage in Rats - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2015)
Background: Early brain injury and cerebral vasospasm are major factors determining outcome for patients who experience subarachnoid hemorrhage (SAH). This study was performed to investigate the potential therapeutic effects of zoledronic acid on cerebral vasospasm in an experimental SAH model. Methods: Fifteen male Sprague Dawley rats were assigned randomly to one of three groups. Animals in Group I were subjected to sham operation and received no treatment after the procedure (sham group, n=5). Animals in Group II were subjected to SAH and received no treatment after SAH induction (SAH group, n=5). Animals in Group III were subjected to SAH and received 0.1 mg/kg intraperitoneal zoledronic acid injection 2 hours after SAH induction (treatment group, n=5). Animals were euthanized 48 hours after the surgical procedures. Neurological deficit grading, basilar artery vasospasm indices, arterial wall thicknesses, and cross-sectional luminal areas were evaluated. Data were statistically compared by Kruskal-Wallis and Mann-Whitney U tests. Results: The treatment group showed a better functional neurological amelioration in comparison to SAH group. However, the difference failed to reach statistical significance. In the treatment group, mean basilar artery vasospasm index and mean basilar artery wall thickness were found to be significantly smaller than those of the SAH group, while mean basilar artery cross-sectional luminal area in the treatment group was insignificantly greater than that of the SAH group. Conclusions: These findings revealed that intraperitoneal zoledronic acid administration attenuated vasospastic changes such as increased vasospasm index and arterial wall thickness in an experimental rat model of SAH.
Keywords: Cerebral vasospasm; subarachnoid hemorrhage; vascular morphometry; neurological outcome; zoledronic acid; NITRIC-OXIDE SYNTHASE; MESSENGER-RNA; UP-REGULATION; RHO-KINASE; BISPHOSPHONATE; SIMVASTATIN; INVOLVEMENT; INHIBITION; AGONIST; STATINS